Diametric calix[6]arene gold(i) catalysts for intramolecular cyclopropanations of 1, 6-dienynes. Issue 32 (27th July 2022) - Giovanardi, Gabriele; Balestri, Davide; Secchi, Andrea; Cera, Gianpiero
Abstract : Solid-state structural determination of three new species and their general applicability for intramolecular cyclopropanations of 1, 6-dienynes. Abstract : We report a solid-state structural investigation of diametric calix[6]arene-based phosphine gold(i ) cavitands which are characterised by two specific, different 1, 2, 3-alternate conformations in solution and in the solid state. The effect of the specific orientation of phosphines, with respect to macrocycles, was studied in intramolecular cyclopropanation of 1, 6-dienynes. The general applicability of these catalysts was disclosed, delivering a family of polycycles with high yields and functional group tolerance.